2005
DOI: 10.1080/13550280590900553
|View full text |Cite
|
Sign up to set email alerts
|

Autistic disorder and viral infections

Abstract: Autistic disorder (autism) is a behaviorally defined developmental disorder with a wide range of behaviors. Although the etiology of autism is unknown, data suggest that autism results from multiple etiologies with both genetic and environmental contributions, which may explain the spectrum of behaviors seen in this disorder. One proposed etiology for autism is viral infection very early in development. The mechanism, by which viral infection may lead to autism, be it through direct infection of the central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(157 citation statements)
references
References 104 publications
3
150
1
3
Order By: Relevance
“…242 The detrimental neurodevelopmental effects of maternal infection have been attributed, in part, to the induction of inflammatory cytokines. 243 Mouse models for prenatal exposure to maternal infection or inflammation have shown that the challenged offspring demonstrate an altered behavioral phenotype, including deficiencies in social interaction, exploration and sensorimotor gating. [244][245][246] Following maternal challenge with influenza virus, offspring also demonstrate altered gene expression in brain, including genes related to transcription and neurotransmission.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…242 The detrimental neurodevelopmental effects of maternal infection have been attributed, in part, to the induction of inflammatory cytokines. 243 Mouse models for prenatal exposure to maternal infection or inflammation have shown that the challenged offspring demonstrate an altered behavioral phenotype, including deficiencies in social interaction, exploration and sensorimotor gating. [244][245][246] Following maternal challenge with influenza virus, offspring also demonstrate altered gene expression in brain, including genes related to transcription and neurotransmission.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…3 Epidemiological studies have indicated that maternal infections during pregnancy increase the risk for these disorders in the offspring. [4][5][6][7] According to one hypothesis, the maternal cytokine response to infections may play a crucial role in this association, 8 because the induction of cytokines is a fundamental immunological event triggered by virtually any infection. 9 More specifically, it has been suggested that activation of pro-inflammatory cytokines, including interleukin (IL)-1b, IL-6 and tumor necrosis factor (TNF)-a, mediate the neurodevelopmental effects of maternal infections on the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Varying reports have also implicated measles and mumps (Deykin and MacMahon, 1979), cytomegalovirus (Libbey et al, 2005), polyomaviruses (Lintas et al, 2010), and influenza (Atladottir et al, 2012;Deykin and MacMahon, 1979;Shi et al, 2003;Zhang et al, 2010) in the incidence of ASD. Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…Given the diversity of infections that show a connection to the spectrum of autism disorders (Boksa, 2010;Libbey et al, 2005), as well as evidence from MIA models that reaction to infection rather than infection itself may lead to autismrelated symptoms (Shi et al, 2003), a possible common etiology may be the influence of the immune system (Gottfried et al, 2015;Lintas et al, 2010;Zhang et al, 2010). Cytokines, small cell-signaling proteins that act as immunomodulatory and endocrine messengers, have been implicated throughout the process of CNS development (Boulanger, 2009;Jones and Thomsen, 2013).…”
Section: Cytokinesmentioning
confidence: 99%